Implementasi Pembelajaran Bahasa Arab dalam Menumbuhkan Sikap Moderasi Beragama dengan Menggunakan Media Youtube di TPQ Al-Hikmah Bandar Lampung - Muhammad Zaky Sya'bani; Munawaroh; Arinda Abelina; Bella Sintya Dewi (Al Mufid, 2023)
Arabic is often referred to as the language of Islam, Of course this can be used as a language of communication for Muslims, However, there are some Muslims who don't like it and find it difficult to learn Arabic. This is due to a lack of intention and interest in learning Arabic. Despite all the difficulties in learning Arabic, one of the main keys is to have the intention and open attitude and accept all the lessons that exist, one of the attitudes that we want to develop in learning Arabic is an attitude of religious moderation. Arabic language learning has actually been taught at TPQ Al-Hikmah Bandar Lampung, but has not yet instilled an understanding regarding religious moderation. Religious moderation is a basic foundation that must be instilled in students from an early age. This activity aims to provide assistance in fostering an attitude of religious moderation in learning Arabic using YouTube media. From the analysis of the results of this activity, there is an increase in students' motivation in learning Arabic and having a moderation attitude in religion. From this research it can be concluded that the implementation of Arabic language learning in fostering an attitude of religious moderation using YouTube media is effective in cultivating students' attitudes that have a moderate and dignified character.